Analisis Penerapan Teknologi Informasi PadaKualitas Sistem Informasi Akuntansi Dalam Pelayanan Rawat Inap (Studi Kasus di RSUD Aek Kanopan Kabupaten Labuhanbatu Utara) - Siti Ardianti; Hendra Harmain; Nurul Inayah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine and answer the question of how the results of the analysis of the application of information technology, to know whether the accounting information system is already qualified in RSUD AEK Kanopan. Application of technology to obtain accurate information required special applications. In RSUD AEK Kanopan itself in the preparation of financial reports using SIMDA application that has been established by The Local Government of North Labuhanbatu. With a supporting application is expected to be able to get accountable information and flexibility, especially in the field of accounting for financial statements that are used today. Services provided in the form of inpatient and outpatient services are a source of revenue realization of Local Government budgets. This study uses a qualitative approach to the type of research descriptive study. The object of this study is an employee associated with information technology in the field of accounting at AEK KANOPAN Hospital, North Labuhanbatu Regency. Data collected through observation, interviews, and documentation related to thesis research. Based on data analysis, the results showed that AEK Kanopan hospital has implemented information technology but there are still obstacles in the application of the old information technology, namely SIMDA, although the Ministry of Home Affairs has issued a SIPD system to support the development and development of applications in each region nationally.